The Role of B Cells in Adult and Paediatric Liver Injury - Patel, Arzoo M.; Liu, Yuxin S.; Davies, Scott P.; Brown, Rachel M.; Kelly, Deirdre A.; Scheel-Toellner, Dagmar; Reynolds, Gary M.; Stamataki, Zania (Frontiers in Immunology, 2021)
B lymphocytes are multitasking cells that direct the immune response by producing pro- or anti-inflammatory cytokines, by presenting processed antigen for T cell activation and co-stimulation, and by turning into antibody-secreting cells. These functions are important to control infection in the liver but can also exacerbate tissue damage and fibrosis as part of persistent inflammation that can lead to end stage disease requiring a transplant. In transplantation, immunosuppression increases the incidence of lymphoma and often this is of B cell origin. In this review we bring together information on liver B cell biology from different liver diseases, including alcohol-related and metabolic fatty liver disease, autoimmune hepatitis, primary biliary and primary sclerosing cholangitis, viral hepatitis and, in infants, biliary atresia. We also discuss the impact of B cell depletion therapy in the liver setting. Taken together, our analysis shows that B cells are important in the pathogenesis of liver diseases and that further research is necessary to fully characterise the human liver B cell compartment.